EARLY SOUND RECORDINGS academic research and practice. - Moreda Rodríguez, Eva.; Stanovi?, Inja. ([S.l.] : ROUTLEDGE, 2023)
The use of historical recordings as primary sources is relatively well established in both musicology and performance studies and has demonstrated how early recording technologies transformed the ways in which musicians and audiences engaged with music. This edited volume offers a timely snapshot of a wide range of contemporary research in the area of performance practice and performance histories, inviting readers to consider the wide range of research methods that are used in this ever-expanding area of scholarship. The volume brings together a diverse team of researchers who all use early recordings as their primary source to research performance in its broadest sense in a wide range of repertoires within and on the margins of the classical canon - from the analysis of specific performing practices and parameters in certain repertoires, to broader contextual issues that call attention to the relationship between recorded performance and topics such as analysis, notation and composition. Including a range of accessible music examples, which allow readers to experience the music under discussion, this book is designed to engage with academic and non-academic readers alike, being an ideal research aid for students, scholars and performers, as well as an interesting read for early sound recording enthusiasts.
Keywords: Sound recordings -- History; Sound recordings -- Sources; MUSIC / Recording & Reproduction; MUSIC / History & Criticism